2006
DOI: 10.1634/stemcells.2005-0196
|View full text |Cite
|
Sign up to set email alerts
|

Human Side Population Keratinocytes Exhibit Long-Term Proliferative Potential and a Specific Gene Expression Profile and Can Form a Pluristratified Epidermis

Abstract: The aim of the present study was to characterize human side population (SP) epidermal keratinocytes isolated from primary cell cultures. For that purpose, keratinocytes were isolated from normal adult breast skin samples and the Hoechst 33342 exclusion assay described for hematopoietic cells was adapted to keratinocytes. Three types of keratinocytes were studied: the SP, the main population (MP), and the unsorted initial population. SP keratinocytes represented 0.16% of the total population. In short-term cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
7

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 34 publications
6
67
0
7
Order By: Relevance
“…Similar to our observations, transcriptional profiling of SP cells from several non-malignant tissues showed that more genes were upregulated than downregulated and included genes associated with multi-drug resistance, regulation of transcription, cell signalling, Notch and Wnt pathways (Liadaki et al, 2005;Behbod et al, 2006;Larderet et al, 2006). Side population fraction cells examined in our studies have upregulated genes that are involved in pathways modulating stemness, including MYC, FGF1, OCT4, KLF4, NOTCH2 and WNT.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to our observations, transcriptional profiling of SP cells from several non-malignant tissues showed that more genes were upregulated than downregulated and included genes associated with multi-drug resistance, regulation of transcription, cell signalling, Notch and Wnt pathways (Liadaki et al, 2005;Behbod et al, 2006;Larderet et al, 2006). Side population fraction cells examined in our studies have upregulated genes that are involved in pathways modulating stemness, including MYC, FGF1, OCT4, KLF4, NOTCH2 and WNT.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, there were more upregulated stem cell genes in SP cells. These features are consistent with previous reports on enrichment in genes associated with growth and developmental pathways in SP cells from normal tissues (Behbod et al, 2006(Behbod et al, , 2006Larderet et al, 2006). In addition, several of the upregulated genes, including ABCG2, BMP1/2, FGF1, IGF1, MYC, SOX1/2, WNT1 and NOTCH2, have been recently associated with cancer stem cells and tumour-initiating cells in lung cancer and other tumour types, as well as with epithelial-tomesenchymal transition in tumours with poor prognosis (Fan et al, 2006;Moustakas and Heldin, 2007).…”
Section: Analysis and Validation Of Gene Expression In Sp And Non-sp supporting
confidence: 93%
“…A similar finding was also noted in cultured epidermal keratinocytes [86]. These results suggest that clonal expansion of "quiescent" limbal SCs is less apt on 3T3 fibroblast feeder layers than "activated" limbal SCs, which generate sufficient numbers of TACs.…”
Section: Will Restoration Of Niche Support Be Critical For Ex Vivo Exsupporting
confidence: 82%
“…Initial reports suggested a role for p63 in epithelial stem cell maintenance (5,6). However, the finding that p63 is not enriched in epidermal stem cells challenges this notion (7)(8)(9)(10). In contrast, we previously demonstrated that TAp63 is required for the commitment to stratification during epidermal morphogenesis, a process that is mediated, in part, by induction of AP-2␥ (11,12).…”
mentioning
confidence: 78%